Effect of merging road design on motorcyclists behavior during merging onto urban expressway - Ammar bin Adnan (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
The riding education programs in Malaysia does not focus on the perception training in general, more specifically, it does not equip motorcyclists with a proper and safe hazard anticipation procedure to merge in traffic. In addition, the merging area also was not well designed that indirectly limit the awareness of road safety among the motorcyclists. Thus, a research on this particular area is needed. This study focused on the effect of merging road design on motorcyclists' behavior during merging onto urban expressway. Two experiments were run for this study. For the first experiment, the objectives are: (i) to evaluate the motorcyclists' head check behavior during merging onto urban expressway; and (ii) to analyze the effect of the merging lane length on the head check behavior during merging onto urban expressway. One-thousand-six-hundred motorcyclists were observed at sixteen scenario locations with the range of merging lane length between 20 to 300 meters. The dependent variable was the percentage of head checks. If a motorcyclist performs a head check toward the target zone while in the launch zone, he or she was scored 1, if not they were scored 0. It was found that the percentage of motorcyclists who did not performed a head check (73.9%) is higher than the percentage of motorcyclists who did perform a head check (26.1%), and the difference between the percentages is significant. In term of the effect of the length of the merging lane, the effect follows a cubic regression line model (y = 93.1 – 1.54X + 9.38E-3X2 – 1.76E-5X3) with the closest correlation value (R2) of 0.64 in comparison to the other two models tested – linear and quadratic regression line model. Analyzing the cubic model, It was revealed that the average length of merging lane (between 129 – 227 meters) was the best length to be considered as a safe merging lane length in term of promoting the head check performance among motorcyclists. For the second experiment, the objectives are: (i) to asses the motorcyclists' entering position during merging onto urban expressway; and (ii) to examine the effect of hatched marking length on entering position among motorcyclists during merging onto urban expressway. Three-thousand-two-hundred motorcyclists were observed at sixteen scenario locations with the range of hatched marking length between 13 to 127 meters. The dependent variable was the percentage of entering position. If a motorcyclist merge into the expressway between the nose and the end of the dotted line of merging lane, he or she was scored 1, if they did not they scored 0. It was found that the percentage of motorcyclists who merge safely (94.5%) is higher than the percentage of motorcyclists who performed head check (5.5%), and the differences between the percentages is significant. In term of the effect of the length of hatched marking area, motorcyclists perform almost perfectly for scenarios with hatched marking length less than 63 meters. For the hatched marking length above 63 meters the decreasing pattern in safe entering position was shown – the longer the hatched marking length the lower percentage of safe entering position. It was found that, the effect follows a linear trend line model (y = -0.7443x + 143.81) with the correlation value (R2) of 0.9114. This result reveals that in order to promote a safe entering position among motorcyclists during merging in urban expressway, the length of the hatched marking should not more than 63 meters. These findings provide useful information for road users and road safety organizations to further improve the standard of Malaysian road safety.